. - Cisternas Ampuero, Cristián (Revista Chilena de Literatura, 2003)
This essay attempts to discuss the concept of .the other flaneur. (the aesthetic traveller of the pre-modern city) in the early poetry and some essays (particularly, Evaristo Carriego) of Jorge Luis Borges. The main idea is that the concept of .the other flaneur. allows us to comprehend the aesthetics of young Borges in relation to the poetic image of the city, the philosophy of the I (myself) in front of the Other (one) and the relationship of the subject with its literary context.